A Brief Review on Determination of Acenocoumarol in Biological and Pharmaceutical Specimens: Analytical Methodologies. (11th April 2022) - Chaudhari, Suraj R.; Mhaske, Prajakta D.; Shirkhedkar, Atul A.
Abstract: Acenocoumarol is an oral anticoagulant medicinal agent is frequently prescribed for the prophylaxis and the management of thromboembolic events. Acenocoumarol is prescribed in the form of racemic mixture and S- form is a more influential isomer. Acenocoumarol starts quickly with action and absorption, and the effect lasts for 15–20 h. In most patients, the therapeutic prothrombin range is caused 36 h after the primary dose. This review offers a detailed overview of the various analytical methodologies published in the literature from 1976 to uptil now for evaluation acenocoumarol and its combinations in specimens. The present review also stated the chiral analytical methods for the quantification of its enantiomers. A detailed study of the work revealed several analytical methodologies are routinely used for estimation of acenocoumarol includes UV/Vis-Spectrophotometry, liquid chromatography-mass spectrophotometry, high-performance liquid-chromatography, gas chromatography, high-performance thin-layer chromatography, capillary electrophoresis, Fourier-transform infrared spectroscopy and many miscellaneous techniques. Pharmaceutical analysis carried out the prominent task to understand the knowledge of the physicochemical properties of the medicinal agent; since the establishment of a new analytical method is still a challenging task for a research scientist. Thus, the present review will help to research scientist for the development of new analytical methods for the acenocoumarol.